Judicial Mediation: Is Reconciliation Impossible in Divorce Cases? - Syaikhu; Sabarudin Ahmad; Muhammad Luthfi Setiarno Putera (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2023)
Judicial mediation attempts to realize the principle of peace in civil cases, however, in its implementation in religious courts there is still minimal success in producing peace agreements, especially in divorce cases. This research aims to analyze whether it is impossible to reconcile the parties in a divorce case through judicial mediation. This research is empirical legal research with a case approach. The data collection methods involve observation, interviews, and documentation. These data are then validated using the triangulation method. After data validation, the next step is to analyze using an analytical method using the theory of legal objectives. Research findings show that successful mediation in divorce cases is not impossible, it's just that divorce cases are very difficult to reconcile, because the parties who submit divorce cases to court usually have reached the climax of domestic problems, and some have not lived together for a long time.